Perbandingan Keberkesanan Penggunaan Lintasan Pejalan Kaki Isyarat Kawalan Masa Tetap Dan Butang Tekan - Abd Wahab, Muhd. Firdaus (Universiti Sains Malaysia, 2006)
Pedestrian crossing should be provided at junction where pedestrian volume is very high. The principal in designing this type of traffic control system is to minimize pedestrian delay and increase pedestrian safety. There are couple of factors that cause the delay such as limiting green time for pedestrian, pedestrian factor and other. However, research on pedestrian crossing is quite new in Malaysia. Therefore, the objective of this research is to study pedestrian behavior at signalized pedestrian crossing in Penang which will give emphasis on aspect of pedestrian delay, crossing time, average speed and crossing occupation time. Thus, with the results obtained, suitable action suggested to provide a higher level of service to the road users especially pedestrian.